2008
DOI: 10.2355/isijinternational.48.1626
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Texture, Grain Boundary Characteristics and Mechanical Properties of a Cold Rolled and Annealed Martensitic Steel

Abstract: The microstructural and textural evolution and changes in Grain Boundary Character Distribution (GBCD) during annealing of a prior cold worked (30 %, 50 % and 80 %) Fe-C martensitic steel have been studied, and correlated with mechanical properties. It has been demonstrated that ultrafine grains in the range 50-250 nm can be obtained by choosing appropriate amounts of cold rolling and annealing. Increasing the annealing temperature in all the three materials produces the expected results, namely decrement of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…This type of processing and heat treatment has been proved to affect greatly the microstructure of martensitic steels. Ghosh et al [69] analysed the microstructural changes of a low carbon martensitic steel (0.17 wt% C) after cold rolling and annealing. They found that high thickness reduction cold rolling (50% and 80% thickness reduction) plus annealing at 700 ˚C resulted in the partial recrystallisation of martensite forming…”
Section: Jethete M152mentioning
confidence: 99%
See 1 more Smart Citation
“…This type of processing and heat treatment has been proved to affect greatly the microstructure of martensitic steels. Ghosh et al [69] analysed the microstructural changes of a low carbon martensitic steel (0.17 wt% C) after cold rolling and annealing. They found that high thickness reduction cold rolling (50% and 80% thickness reduction) plus annealing at 700 ˚C resulted in the partial recrystallisation of martensite forming…”
Section: Jethete M152mentioning
confidence: 99%
“…Figure 45: Micrographs of low carbon martensitic steel after: a) No processing (Initial microstructure), b) 30% reduction cold rolling, c) 50% reduction cold rolling and d) 80% reduction coldrolling [69]. …”
mentioning
confidence: 99%
“…In recent years, some investigations on the formation of the inclusions in steel were carried out with thermodynamic analysis. [5][6][7][8][9][10][11] For example, Wang et al [7] investigated the effect of oxide component content on the low melting point zone in the Al 2 O 3 •SiO 2 •CaO•MgO system using FactSage software. It was found that the low melting point zone becomes wide with the increase in CaO content within the range of 0-30 mass% and the decrease in SiO 2 content within the range of 5-25 mass%.…”
Section: Introductionmentioning
confidence: 99%
“…Deformation and annealing texture development in steels have been studied in details. [5][6][7][8][9][10] In cold-rolled SUS301 steel, it was found that the main texture component was characterized by f110gh112i Brass, f110gh001i Goss and f112gh111i Copper components. 6) In ferritic stainless steels and martensitic steels, -fiber and -fiber were observed to be the dominant texture components.…”
Section: Introductionmentioning
confidence: 99%
“…6) In ferritic stainless steels and martensitic steels, -fiber and -fiber were observed to be the dominant texture components. [8][9][10] Although the mechanical properties of multi-layered materials have been extensively studied, 1) few reports have been addressed on the texture development of the structural multi-layered materials during cold-rolling and subsequent annealing. It is considered that the different mechanical properties of the components in composites will obviously affect the stress and strain states during rolling and further influence the crystallographic texture development in the component steels.…”
Section: Introductionmentioning
confidence: 99%